2001
DOI: 10.1007/s11745-001-0750-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of triterpenoids and sterols on human immunodeficiency virus‐1 reverse transcriptase

Abstract: Fifty-five triterpenoids consisting of 19 tetracyclic, 32 pentacyclic, and 4 incompletely cyclized triterpenoids, and 2 sterols, mostly isolated from various plant and fungal materials, were examined for their inhibitory effects on a purified human immunodeficiency virus type 1 (HIV-1) reverse transcriptase. Twenty triterpenoids and one sterol showed inhibitory effects with 50% inhibition concentration (IC50) values less than 5.0 microM. Among these cycloartenol ferulate (IC50 = 2.2 microM), 24-methylenecycloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 43 publications
(50 reference statements)
1
52
0
2
Order By: Relevance
“…Previous studies have demonstrated that euphol exerts antiviral effects by inhibiting reverse transcriptase in purified human immunodeficiency virus type 1 (12) and inhibiting the Epstein-Barr virus early antigen activation induced by the tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA) (13). The anti-inflammatory effects of euphol have been demonstrated to be associated with the inhibition of the activation of nuclear factor-κB (14), downregulation of tumor necrosis factor-α and cyclooxygenase-2 (15), inhibition of the T cell-mediated immune response (15), and the reduction of protein kinase C/extracellular signal-regulated protein kinase signaling activation (16).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that euphol exerts antiviral effects by inhibiting reverse transcriptase in purified human immunodeficiency virus type 1 (12) and inhibiting the Epstein-Barr virus early antigen activation induced by the tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA) (13). The anti-inflammatory effects of euphol have been demonstrated to be associated with the inhibition of the activation of nuclear factor-κB (14), downregulation of tumor necrosis factor-α and cyclooxygenase-2 (15), inhibition of the T cell-mediated immune response (15), and the reduction of protein kinase C/extracellular signal-regulated protein kinase signaling activation (16).…”
Section: Introductionmentioning
confidence: 99%
“…Sitosterol possesses antihyperlipoproteinaemic, antibacterial and antimicotic activity and has been shown to act as inhibitor of tumor promotion in vivo (Yasukawa et al, 1991) and to inhibit carcinogenesis (Raicht et al, 1980). Stigmasterol was found to markedly inhibit tumor promotion in two-stage carcinogenesis in mice (Kasahara et al, 1994;Yasukawa et al, 1991) and to exhibit significant inhibitory effect on HIV reverse transcriptase (Akihisa et al, 2001). A mixture of stigmasterol and sitosterol was shown to possess anti-inflammatory activity after topical application (Gomez et al, 1999).…”
Section: Sterolmentioning
confidence: 99%
“…Campestanol is distributed in plant oils consumed in human diets, which is not accumulated when fed and incorporated into the diet may block cholesterol absorption (Xu et al, 1999). Stigmastan-3-ol has been reported to inhibit HIV-1 reverse transcriptase (Akihisa et al, 2001). Sterols with C-7 double bond occur relatively seldom in plants.…”
Section: Sterolmentioning
confidence: 99%
“…A method to obtain large quantities of both triterpene acids from olive-mill wastes has been reported by our group [5], and these compounds could be useful to semi-synthesize other biologically or chemically significant products. In fact, oleanenes possess a 4,4,10-trimethylsubstituted trans-decalin system with the H-atom at C (9) in an a-position (A-and Brings), such as drimane sesquiterpenes or related compounds with remarkable biological, olfactory, and fixative properties [6 -8]. Moreover, the bicyclic system formed by the D-and E-rings is related to naturally occurring tricyclic triterpenes such as camelliols A and B [9], and other bicyclic and tetracyclic triterpenes (preoleanatetraene and seco-C-oleanene, resp.)…”
mentioning
confidence: 99%